PENGARUH HARGA DISKON DAN PROMOSI TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA SUPPLEMENT BLACKMORES DI SURAKARTA - Widya Wijayanti; Endang Winarsih; Santosa Tri Prabawa (JURNAL WIRANOMIKA, 2024)
The aim of this research is to determine the effect of discount prices and promotions on customer loyalty with customer satisfaction as a mediating variable in Blackmores supplements in Surakarta. This research was conducted at the Blackmores Supplement health stand at The Park Solo Baru Mall. The population in this study were Blackmores Supplement consumers with a total of 136 consumers. The number of Blackmores Supplement consumers was 136 people, so the research took a sample of 100 people or 70.4% of the total population. The basis for this sampling is random sampling according to the specified sample size. Data collection used was personal documentation and questionnaires. The data analysis method used in this research is by using a structural equation model (Structural Equation Modeling). The path analysis used is Partial Least Squares (PLS), using Smart-PLS 3.0 software. The results of this research show that discount prices have a significant effect on Blackmores Supplement customer satisfaction in Surakarta, Promotions have a significant effect on Blackmores Supplement customer satisfaction in Surakarta, Customer satisfaction has a significant effect on Blackmores Supplement customer loyalty in Surakarta, Discount prices have a significant effect on Blackmores Supplement customer loyalty in Surakarta, Promotion has a significant effect on Blackmores Supplement customer loyalty in Surakarta, There is a significant influence of discount prices on customer loyalty through Blackmores Supplement customer satisfaction in Surakarta and There is a significant influence of Promotion on customer loyalty through Blackmores Supplement customer satisfaction in Surakarta.Â Keywords : discount prices, promotions, customer loyalty , customer satisfactionÂ